PENGARUH PENAMBAHAN KOTORAN UNGGAS YANG BERBEDA PADA MEDIA BUDIDAYA TERHADAP PERTUMBUHAN CACING SUTRA (Tubifex sp.) - Katijah, Katijah; Rahmayanti, Fitria; Ibrahim, Yusran; Febrina, Citra Dina (JURNAL AKUAKULTURA, 2022)
This study aims to determine the effect of using different poultry manure as a medium for its culture. The method used in this study is an experimental design using a random design with four treatments and three replications. The factors tested were the addition of different poultry manure such as without the addition of poultry manure (P0), the addition of free-range chicken manure (P1), the addition of laying hen manure (P2), and the addition of quail manure (P3). The results of ANOVA analysis using SPSS 20.0 showed that the addition of different poultry manure had a significant effect on the absolute biomass of tubifex worms. Duncan test results showed that the absolute biomass of tubifex worms in the P3 treatment (addition of quail manure) was significantly different from the other treatments. In addition, the media added with quail manure produced the highest absolute biomass (243,33 gram) compared to other treatments.